Higher toughness steel alloy weld deposit and flux-cored welding electrode for producing higher toughness steel alloy weld deposit
By using flux-core welding electrodes and tubular steel strips, the chemical composition and cooling process of the weld are controlled to form an optimized ferrite structure, which solves the problem of insufficient toughness of the weld deposits in the prior art and achieves high toughness and excellent weld production.
Patent Information
- Application Number
- CN202010830899.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-20
- Filing Date
- 2020-08-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-08-18
AI Technical Summary
It is difficult to produce steel alloy weld deposits with high toughness and excellent structural structure in the prior art, resulting in insufficient strength and toughness of the weld.
Flux-core welding electrodes are used, and the flux-core contains a specific proportion of zirconium, aluminum, magnesium, manganese, nickel, boron, sodium oxide, titanium dioxide and fluoride. Combined with tubular steel strips, it is optimized through fine chemical composition and cooling process control. Ferrite tissue.
It has achieved the production of steel alloy weld deposits with high toughness and excellent structural structure, improved the strength and toughness of the weld, and met the chemical composition requirements of the AWS A5.20 E71T-12 specification.
Smart Images

Figure CN112404792B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to flux-cored welding electrodes for producing higher toughness steel alloy weld deposits, and to the higher toughness weld deposits themselves. Background Art
[0002] Essentially, all steel is a mixture of iron and carbon, or more accurately, an alloy of iron and carbon. However, even so-called plain carbon steel has small but specified amounts of manganese and silicon, as well as small (usually unavoidable) amounts of phosphorus and sulfur. Plain carbon steel can have a carbon content as high as 2.0%, but such alloys are rare. Commercially available steel typically has a carbon content ranging from about 0.05% to about 1.0%.
[0003] When heated to 912°C (1674°F), iron changes from one atomic arrangement to another in a process called transformation. This transformation occurs not only in pure iron but also in its many alloys; each alloy composition transforms at its own characteristic temperature. It is this transformation that makes it possible to achieve a wide range of properties with a high degree of reproducibility through the use of carefully selected heat treatments.
[0004] A phase diagram is a graphical representation of the equilibrium temperature and composition limits of the phase field and phase reactions in an alloy system. In the iron-cementite system, temperature is plotted vertically and composition is plotted horizontally. Figure 1 (in Chinese) concerns only the composition of the iron-iron carbide system, i.e. what phases exist at each temperature and composition.
[0005] When a steel alloy is cooled rapidly, carbon atoms cannot escape from the iron lattice in an orderly manner. This causes "atomic chaos" and leads to lattice distortion, which can increase hardness, strength, or both (although it may also increase the brittleness of the steel alloy). If the cooling is rapid enough (for example, during quenching), a new structure called martensite may form, although this new structure (an aggregate of iron and cementite) is in the alpha phase.
[0006] Although ordinary carbon steel alloys typically have only three stable phases at room temperature (ferrite, cementite, and pearlite), many different microstructures can be formed through different cooling processes and control of the alloy composition. Summary of the Invention
[0007] The present disclosure generally relates to a flux-cored welding electrode for producing higher toughness steel alloy weld deposits.
[0008] According to one aspect of the present disclosure, a flux-cored welding electrode for producing a relatively high-toughness steel alloy weld deposit comprises a flux core and a tubular steel strip. The flux core may comprise, by weight percentage of the electrode, 0.25%-0.30% zirconium, 0.12%-0.18% aluminum, 0-0.11% silicon, 0.46%-0.52% magnesium, 1.85%-2.05% manganese, 0.35%-0.45% nickel, 0.004%-0.008% boron, 0.16%-0.22% sodium oxide, 7.0%-8.0% titanium dioxide, 0-0.50% silicon dioxide, and 0.20%-0.30% fluoride. The fluoride may be selected from the group consisting of lithium fluoride, sodium fluoride, aluminum fluoride, sodium cryolite, potassium fluorosilicate, Teflon, and any combination thereof. The tubular steel strip may contain 0.06%-0.10% carbon, 0.35%-0.40% manganese, and the balance steel, including unavoidable impurities, by weight percentage of the tubular steel strip.
[0009] According to another aspect of this disclosure, flux-cored welding electrodes (such as the welding electrodes described in paragraph
[0008] ) can be used to produce weld deposits of high-toughness steel alloys. The weld deposit may contain 0 to 0.19% silicon by weight of the weld deposit. The weld deposit may further comprise, by weight percentage, 0 to 0.07% oxygen, 0 to 0.01% nitrogen, 0 to 0.03% aluminum, 0 to 0.015% zirconium, 0 to 0.09% titanium, 0 to 0.012% vanadium, 0 to 0.10% chromium, 0 to 0.01% molybdenum, 0 to 0.003% tungsten, 0 to 0.012% niobium, 0 to 0.50% nickel, 0.90% to 1.60% manganese, 0.01% to 0.12% carbon, 0 to 0.35% copper, and 0.0015% to 0.0065% boron.
[0010] It should be understood that the foregoing general description and the following detailed description depict various embodiments and are intended to provide an overview or framework for understanding the nature and features of the claimed subject matter. These accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated within and form part of this specification. The drawings illustrate the various embodiments described herein and, together with the specification, serve to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] The following is a description of the examples depicted in the accompanying drawings. The drawings are not necessarily drawn to scale, and for clarity or simplicity, some features and views may be exaggerated or shown schematically.
[0012] Figure 1A copy of the iron-rich end of the iron-carbon phase diagram (also known as the iron-iron carbide phase diagram or the iron-cementite phase diagram) is shown;
[0013] Figure 2 shows an example cross section of a flux-cored welding wire; and
[0014] Figure 3 Example welding equipment for flux-cored arc welding (FCAW) using a wire electrode is shown.
[0015] The foregoing summary and the following detailed description will be better understood when read in conjunction with the accompanying drawings. It should be understood that the claims are not limited to the arrangements and instrumentality shown in the drawings. Furthermore, the appearance shown in the drawings is one of many decorative appearances that can be employed to achieve the described function of the device. DETAILED DESCRIPTION
[0016] In the following detailed description, specific details are set forth in order to provide a thorough understanding of embodiments of the present disclosure. However, those skilled in the art will appreciate that the disclosed examples may be practiced without some or all of these specific details. For the sake of brevity, well-known features or processes may not be described in detail. Furthermore, similar or identical reference numerals may be used to identify common or similar elements.
[0017] One or more specific embodiments of this disclosure will be described below. To provide a concise description of these embodiments, not all features of the actual implementation may be described in the specification. It should be understood that, as in any engineering or design project, numerous implementation-specific decisions must be made to achieve the developer's specific goals, such as complying with system-related and business-related constraints, which may change with the implementation. Furthermore, it should be understood that such development work may be complex and time-consuming, but will be a routine task of design, production, and manufacturing for those skilled in the art who enjoy the benefits of this disclosure.
[0018] When introducing elements of various embodiments of the present disclosure, the articles "a," "an," "the," and "said" are intended to mean that there are one or more of the elements. The terms "comprising," "including," and "having" are intended to be inclusive and mean that there may be additional elements other than the listed elements.
[0019] According to this disclosure, the newly deposited weld metal has a novel and unique microstructure. Specifically, the solid weld metal is a unique combination of ferrite (phase) structures, which are products of the transformation from an austenitic phase structure existing above the initial Ac3 transformation temperature of this composition. The austenitic structure and its composition, along with the cooling rate, will determine the "quality" of the final ferrite structure. Figure 1 The iron-iron carbide phase diagram is shown.
[0020] Furthermore, multi-pass welds have the added benefit of reheating portions of the previously deposited weld to austenite. This reheated area experiences less directional cooling than the newly deposited pool of liquid.
[0021] The mechanical properties of the weld deposit depend on the amount of ferrite in the original deposited state and the amount of ferrite as a product of re-austenitization (heat affected weld metal (HAWM)).
[0022] The amount of HAWM in a multi-pass weld metal is a direct function of the Ac3 temperature (range). The lower the Ac3 temperature of the weld metal, the more HAWM is produced. The Ac3 temperature is determined by the composition of the weld metal. Ferrite stabilizers generally increase the Ac3 transformation temperature (one exception is chromium, which primarily reduces Ac3). Austenite stabilizers generally decrease the Ac3 transformation temperature (one exception is cobalt, which slightly increases Ac3).
[0023] The composition of the weld metal deposit is important because a lower bainitic ferrite structure is the preferred outcome within the range of cooling rates encountered. The composition should produce the lowest Ac3 temperature and, during weld metal deposition, should form inclusions in the liquid, leading to the formation of fine-grained austenite. This characteristic is important because grain boundaries persist in the final ferrite structure. The weld metal should also be relatively clean; inclusions (proportional to the oxygen and nitrogen content) should be kept to a minimum within the slag system.
[0024] The AWS A5.20 (A5.36) specification for the E71T-12 electrode type defines the chemical composition of the full weld metal. These limits restrict how Ac3 can be controlled. Austenite stabilizers are tightly bound. In the T-12 design, the preferred alloying ferrite stabilizer is silicon; this element is limited. Silicon raises the Ac3 temperature, leading to grain growth in the ferrite phase. High silicon levels make the design more welder-friendly. According to the present disclosure, it is possible to achieve the same amount of reaction as the oxygen in the system (from the shielding gas and oxides), but using very low levels of ferrite stabilizers. To this end, all or nearly all of the metallic silicon is removed from the electrode, and the amount of silicon dioxide that is reduced to silicon and enters the weld deposit is limited, thereby achieving no more than a limited amount of silicon in the weld metal (e.g., no more than 0.19 or 0.15 weight percent). The deoxidation function lost by removing the metallic silicon is achieved by more reactive components, which remain in the weld metal in very small amounts. The primary deoxidizers that replace silicon are zirconium and aluminum. Titanium is another possible alternative, but its use may result in titanium levels in the weld metal that may cause embrittlement of the weld metal.
[0025] In summary, this method allows for higher levels of austenitic stabilizers in the weld electrode, which recovers the tensile strength lost due to reduced silicon in the weld deposit. Minimal amounts of ferrite stabilizers in the weld deposit significantly reduce the rise in Ac3 temperature. A more favorable austenite / ferrite ratio results in an increased amount of fine microstructure in multi-pass welds.
[0026] When designing to AWS specification electrode types, minimum requirements for weld deposit chemistry and mechanical properties measured using specified test specimens extracted from AWS grooves must be met. In addition, other testing organizations such as ABS (American Bureau of Shipping) may have unique testing requirements that qualify electrodes for use in specified applications. The purpose of these tests is not to test the full weld metal properties of the electrode, but to predict actual performance when used on a specified base material and electrode. One such test is the ABS 3G butt weld.
[0027] The welding electrode according to this disclosure is designed to have suitable Charpy “V” notch (CVN) toughness down to -76°F. It is generally accepted practice that a CVN value exceeding 20 ft-lbs at the test temperature is considered acceptable for use at that temperature.
[0028] CVN toughness depends on the microstructure, composition, and cleanliness of the weld deposit. Electrodes according to this disclosure should meet the specified chemical composition range for AWS electrode types. AWS also describes the general composition of the slag for each electrode type. Electrodes according to this disclosure may be referred to as "rutile" type, which achieves very good all-position welding with relatively low spatter.
[0029] Within the range of deposit chemistries for each electrode type, the deposit chemistry can be optimized to achieve maximum toughness. One technique is to use a very high ratio of austenite stabilizer to ferrite stabilizer. As this ratio increases, the AC3 transformation temperature decreases; low AC3 temperatures correlate well with CVN toughness. Two reasons for this result are better single-pass microstructure and, more importantly, a greater volume of fine microstructure in multi-pass AWS groove welds.
[0030] According to the present disclosure, welding electrodes are prepared in which the silicon content of the flux core has been removed or reduced. This change reduces the silicon content of the weld metal. Silicon is present in rutile electrodes to react with oxygen and improve weld bead wetting and shape. According to the present disclosure, equivalent oxidation is achieved by using aluminum powder in the flux core. The aluminum powder reacts more completely; very little aluminum is recovered in the weld deposit. Some silicon is still found in the weld metal; this silicon originates from dissolution of the base material into the weld pool and reduction of silicon dioxide in the electrode core.
[0031] Thus, according to the present disclosure, the metal powder in the core will contain almost no metallic silicon. For example, a reduced amount of metallic silicon (≤0.12% or ≤0.11% by weight of the electrode) in the form of silicon-zirconium metal powder can be added to the core as a carrier while zirconium metal is added to the core. In addition, aluminum is used as a substitute for silicon. Thus, zirconium can be added to the core in the form of aluminum-zirconium metal powder to increase both the amount of zirconium and the amount of aluminum. Alternatively, zirconium can be added to the core in the form of nickel-zirconium metal powder. Aluminum can be added to the core in the form of aluminum-zirconium metal powder to further increase the amount of zirconium. According to one aspect of the present disclosure, the core contains 0.12%-0.18% (e.g., 0.16%) aluminum and 0.25%-0.30% (e.g., 0.26%) zirconium by weight of the electrode. This alloy combination, along with up to 0.50% (e.g., 0.44%) silicon dioxide in the flux core by weight of the electrode, results in an all weld metal (AWM) silicon content of less than 0.20% (e.g., less than 0.19% or less than 0.15%) by weight of the weld deposit, and less than 0.015% AWM aluminum by weight of the weld deposit (AWS groove weld test). According to certain aspects of the present disclosure, AWM is less than 0.15% by weight of the weld deposit.
[0032] The above electrode compositions and weld metals may be included in a slag system using clean rutile technology.
[0033] According to one aspect of the present disclosure, a flux-cored welding electrode for producing a relatively high toughness steel alloy weld deposit comprises a flux core and a tubular steel strip. The flux core may comprise, by weight percentage of the electrode, up to 0.50% zirconium, up to 0.25% aluminum, up to 0.7% magnesium, up to 2.5% manganese, up to 0.6% nickel, up to 0.01% boron, up to 0.3% sodium oxide, up to 10% titanium dioxide, and up to 0.50% fluoride. The flux core may additionally comprise up to 0.15% silicon and up to 0.60% silicon dioxide. Zirconium metal, aluminum, and silicon may be added to the flux core in the form of silicon-zirconium metal powder and aluminum-zirconium metal powder. Fluoride, as used in the present disclosure, refers to a metal containing fluoride anions (F - ). The fluoride can be selected from the group consisting of lithium fluoride, sodium fluoride, aluminum fluoride, sodium cryolite, potassium fluorosilicate, Teflon, and any combination thereof. For example, the fluoride can be selected from the group consisting of lithium fluoride, sodium cryolite, Teflon, and any combination thereof.
[0034] According to one aspect of the present disclosure, the core may comprise, by weight percentage of the electrode, 0.25%-0.30% zirconium, 0.12%-0.18% aluminum, 0.46%-0.52% magnesium, 1.85%-2.05% manganese, 0.35%-0.45% nickel, 0.004%-0.008% boron, 0.16%-0.22% sodium oxide, 7.0%-8.0% titanium dioxide, and 0.20%-0.30% fluoride. The core may further comprise 0.08%-0.11% silicon. The core may further comprise 0.42%-0.50% silicon dioxide.
[0035] According to another aspect of this disclosure, the core may comprise, by weight percentage of the electrodes: 0.26% zirconium, 0.16% aluminum, 0.49% magnesium, 1.95% manganese, 0.38% nickel, 0.18% sodium oxide, 7.4% titanium dioxide, and 0.26% fluoride. The core may additionally contain 0.09% silicon. The core may additionally contain 0.44% silicon dioxide.
[0036] The tubular steel strip may contain up to 0.15% carbon and up to 0.5% manganese by weight, with the balance being steel, including unavoidable impurities. For example, the tubular steel strip may contain 0.05%-0.12% carbon and 0.25%-0.50% manganese by weight; or 0.06%-0.10% carbon and 0.30%-0.45% manganese; or 0.07%-0.09% carbon and 0.35%-0.40% manganese by weight.
[0037] According to another aspect of the present disclosure, a relatively high toughness steel alloy weld deposit can be produced using a flux-cored welding electrode, such as the welding electrodes described in paragraphs
[0033] -
[0036] . To increase the toughness of the weld deposit, the amount of silicon in the weld deposit can be minimized. For example, the weld deposit can include 0 to 0.19% silicon, or 0 to 0.15% silicon, by weight of the weld deposit. The weld deposit may further include, by weight percentage of the weld deposit, 0 to 0.12% oxygen (e.g., 0 to 0.07% oxygen), 0 to 0.01% nitrogen, 0 to 0.03% aluminum (e.g., 0 to 0.02% aluminum), 0 to 0.015% zirconium (e.g., 0 to 0.005% zirconium), 0 to 0.09% titanium, 0 to 0.50% nickel, 0.90% to 1.60% manganese, 0.01% to 0.12% carbon, 0 to 0.35% copper (e.g., 0 to 0.020% copper), and 0 to 0.008% boron (e.g., 0.0015% to 0.0065% boron). The weld deposit may further comprise, by weight percentage of the weld deposit, 0 to 0.012% vanadium, 0 to 0.10% chromium, 0 to 0.01% molybdenum, 0 to 0.003% tungsten, and 0 to 0.012% niobium.
[0038] According to one aspect of the present disclosure, the weight percentages of oxygen and nitrogen in a weld deposit can be measured by a LECO combustion test. The weight percentage of boron in a weld deposit (or welding electrode) can be measured by a calibrated arc spark spectrometer.
[0039] Table 1 shows the properties of a weld deposit (Example 1) formed according to the present disclosure.
[0040] Table 1
[0041] Welding experiments using an embodiment of a tubular welding wire according to the present disclosure (Example 1).
[0042]
[0043] Table 1
[0044]
[0045] Table 2 shows the properties of a weld deposit (Example 2) formed according to the present disclosure.
[0046] Table 2
[0047] Welding experiments using an embodiment of a tubular welding wire according to the present disclosure (Example 2).
[0048]
[0049] Table 2
[0050]
[0051] Table 3 shows the properties of a weld deposit (Example 3) formed according to the present disclosure.
[0052] Table 3
[0053] Welding experiments using an embodiment (Example 3) of a tubular welding wire according to the present disclosure.
[0054]
[0055] As shown in Tables 1-3, the as-welded Charpy V-notch (CVN) toughness of the weld deposit at -60°F can be, for example, at least 60 ft-lbs or at least 70 ft-lbs. At -76°F, the CVN toughness of the weld deposit can be, for example, at least 50 ft-lbs or at least 110 ft-lbs. After stress relieving at 1150°F for 4 hours, the CVN toughness of the weld deposit at -60°F can be, for example, at least 40 ft-lbs or at least 75 ft-lbs. After stress relieving at 1150°F for 1 hour, the CVN toughness of the weld deposit at -60°F can be, for example, at least 55 ft-lbs.
[0056] According to one aspect of this disclosure, the weld deposit can be produced by welding in butt welds specified by ABS and groove welds of AWS A5.20 E71T-12, and meets the requirements and limitations of AWS A5.20 E71T-12 for the composition of all weld metals.
[0057] According to one aspect of the present disclosure, a flux-cored wire electrode can be manufactured by providing a strip (or sheath material) and feeding the strip through a forming die that bends the strip and forms it into a shape that can be filled with the components of the flux-coring composition. Typically, the formed shape is a U-shape. The formed sheath is then filled with the flux-coring composition. The wire then passes through a closing die that closes it into a tubular shape, wherein the sheath 30 encapsulates the core 32, thereby forming a flux-cored wire electrode, such as Figure 2 As shown. The flux-cored wire electrode may have a seam 34. The composition of the flux-cored material is typically in powder form, which can be compacted when the encapsulated wire is fed through a drawing die to reduce the diameter of the wire to the final desired diameter.
[0058] According to one aspect of this disclosure, the electrode may comprise 75%-95% sheath and 25%-5% core by weight of the electrode; or 80%-95% sheath and 20%-5% core; or 85%-90% sheath and 15%-10% core. Other ranges for the sheath and core may be feasible and still within the scope of this disclosure.
[0059] Figure 3 An example of a welding apparatus for flux-cored wire arc welding (FCAW) using a welding wire electrode according to the present disclosure is shown. The welding apparatus includes a DC power supply 50, a welding torch 10, a welding wire electrode 14, and means for feeding the welding wire electrode 14 into the welding torch 50. An example of the means for feeding the welding wire electrode is shown in... Figure 3 1 and 2. Shielding gas 16 may be supplied to the welding process by a gas nozzle 12 in the welding gun 10. The wire electrode 14 may have a sheath and a core having a flux core composition as described herein. An arc 18 is formed between the wire electrode 14 and one or more workpieces 11, 13 to form a molten weld pool 15. Shielding gas 16 may be supplied to the welding process by an external source 17. For an FCAW process in which the welding gun is coupled to a DC power source, the shielding gas may be a mixture of Ar and CO2 mixed in a ratio of 75% Ar / 25% CO2, 80% Ar / 20% CO2, 82% Ar / 18% CO2, 90% Ar / 10% CO2, or 95% Ar / 5% CO2. Alternatively, 100% CO2 may be used as the shielding gas, or a ratio of 95% Ar / up to 5% O2 to stabilize the arc, or other suitable shielding gas blends.
[0060] The various aspects and embodiments disclosed herein are not intended to be limiting. Other embodiments may be used, and other changes may be made, without departing from the spirit or scope of the subject matter presented herein. It will be readily understood that, as generally described herein and illustrated in the accompanying drawings, the various aspects of the present disclosure may be arranged, substituted, combined, separated, and designed in a variety of different configurations, all of which are contemplated herein.
Claims
1. A flux-cored welding electrode for producing a relatively high toughness steel alloy weld deposit, comprising: a core; and Tubular steel strips; The drug core comprises the following components in weight percentage of the electrode: 0.25%-0.30% of metallic zirconium, 0.12%-0.18% of metallic aluminum, 0-0.11% silicon, 0.46%-0.52% magnesium, 1.85%-2.05% manganese, 0.35%-0.45% nickel, 0.004%-0.008% boron, 0.16%-0.22% sodium oxide, 7.0%-8.0% titanium dioxide, 0-0.50% silica, and 0.20%-0.30% fluoride.
2. The flux-cored welding electrode of claim 1, wherein the flux core further comprises 0.08%-0.11% silicon based on the weight percentage of the electrode.
3. The flux cored welding electrode of claim 1, wherein the flux core further comprises 0.42% to 0.50% silicon dioxide based on the weight percentage of the electrode.
4. The flux-cored welding electrode of claim 1, wherein the fluoride is selected from the group consisting of lithium fluoride, sodium fluoride, aluminum fluoride, sodium cryolite, potassium fluorosilicate, polytetrafluoroethylene, and any combination thereof.
5. The flux-cored welding electrode of claim 4, wherein the fluoride is selected from the group consisting of lithium fluoride, sodium cryolite, polytetrafluoroethylene, and any combination thereof.
6. The flux cored welding electrode of claim 1, wherein the flux core comprises zirconium and silicon in the form of silicon-zirconium metal powder.
7. The flux cored welding electrode of claim 1, wherein the flux core comprises aluminum and zirconium in the form of an aluminum-zirconium metal powder.
8. The flux cored welding electrode of claim 1, wherein the zirconium, the aluminum and the silicon in the flux core consist of zirconium, aluminum and silicon in the form of silicon-zirconium and aluminum-zirconium metal powders.
9. The flux-cored welding electrode of claim 1, wherein the tubular steel strip comprises, by weight percentage of the tubular steel strip: 0.05%-0.12% carbon, 0.30%-0.45% manganese, and The remainder of steel, including unavoidable impurities.
10. The flux-cored welding electrode of claim 9, wherein the tubular steel strip comprises, by weight percentage of the tubular steel strip: 0.06%-0.10% carbon, 0.35%-0.40% manganese, and The remainder of steel, including unavoidable impurities.
11. The flux-cored welding electrode according to claim 1, wherein: The tubular steel strip comprises, by weight percentage of the tubular steel strip: Up to 0.15% carbon, Up to 0.50% manganese, and The remainder of steel, including unavoidable impurities.
12. A relatively high toughness steel alloy weld deposit produced using the flux-cored welding electrode of claim 1, wherein the relatively high toughness steel alloy weld deposit comprises, by weight percentage: 0 to 0.19% silicon.
13. The higher toughness steel alloy weld deposit of claim 12 further comprising, by weight percentage: 0 to 0.15% silicon.
14. The higher toughness steel alloy weld deposit of claim 12, further comprising, by weight percent: 0 to 0.07% oxygen; 0 to 0.01% nitrogen; 0 to 0.03% aluminum; 0 to 0.015% zirconium; 0 to 0.09% titanium; 0 to 0.50% nickel; 0.90% to 1.60% manganese; 0.01% to 0.12% carbon; 0 to 0.35% copper; and 0 to 0.008% Boron.
15. The higher toughness steel alloy weld deposit of claim 14, wherein the weld deposit comprises, by weight percentage: 0 to 0.012% vanadium.
16. The higher toughness steel alloy weld deposit of claim 14, wherein the weld deposit comprises, by weight percentage: 0 to 0.10% chromium.
17. The higher toughness steel alloy weld deposit of claim 14, wherein the weld deposit comprises, by weight percentage: 0 to 0.01% molybdenum.
18. The higher toughness steel alloy weld deposit of claim 14, wherein the weld deposit comprises, by weight percentage: 0 to 0.003% tungsten.
19. The higher toughness steel alloy weld deposit of claim 14, wherein the weld deposit comprises, by weight percentage: 0 to 0.012% niobium.
20. The higher toughness steel alloy weld deposit of claim 14, wherein the weld deposit comprises, by weight percentage: 0.0015% to 0.0065% boron.
21. The higher toughness steel alloy weld deposit of claim 12, wherein: The weld deposit has an as-welded Charpy V-notch (CVN) toughness of at least 60 foot pounds at -60°F.
Citation Information
Patent Citations
Self-protection flux-cored wire suitable for oil and gas pipeline and preparing method of flux-cored wire
CN106541225A
Flux-cored wire for gas-shielded arc welding
US20170274482A1